2014
DOI: 10.1016/j.ijggc.2014.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater hydrogeochemistry in injection experiments simulating CO2 leakage from geological storage reservoir

Abstract: a b s t r a c tGeologic carbon sequestration has the potential to reduce greenhouse gas concentrations in the atmosphere. However, one barrier to large scale implementation is concern for water quality degradation from leakage of high CO 2 fluids into drinking water aquifers. The hydrogeochemical response to simulated CO 2 leakage was studied to estimate major and trace element release and to develop criteria for water quality monitoring and risk assessment. In this study, approximately 3100 L aquifer water en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…These authors postulate that the unrealistically high water / rock ratios, reactive surface area (due to disaggregation), and mixing in batch experiments maintain mineral phases under saturated and thus mass transfer rates artificially high. Only Yang et al (2014b) found comparable release rates for both experimental types.…”
Section: Field Experimentsmentioning
confidence: 87%
See 4 more Smart Citations
“…These authors postulate that the unrealistically high water / rock ratios, reactive surface area (due to disaggregation), and mixing in batch experiments maintain mineral phases under saturated and thus mass transfer rates artificially high. Only Yang et al (2014b) found comparable release rates for both experimental types.…”
Section: Field Experimentsmentioning
confidence: 87%
“…In terms of impact on drinking water quality, aside from a limited number of exceptions, trace element concentrations remained well below national and international drinking water limits in all field experiments in which they were measured Cahill et al, 2014;Kharaka et al, 2010;Mickler et al, 2013;Peter et al, 2012;Trautz et al, 2013;Yang et al, 2013a;Yang et al, 2014b). Exceptions included Al values over 10x the WHO guidelines (Cahill et al, 2014), two samples that exceeded Ni drinking water levels , and some pH, Fe, Mn and Zn values that exceeded secondary standard levels where effects are deemed to be cosmetic or aesthetic (Yang et al, 2014b).…”
Section: Field Experimentsmentioning
confidence: 92%
See 3 more Smart Citations